Opportunities and Challenges of Indonesian NERS Graduates in the ASEAN Job Market Competition through MRA Nursing 2025 - Munawaroh, Magfirohtul (Fakultas Ilmu Kesehatan Universitas Gresik, 2025)
Graduates of NERS Indonesia face both challenges and opportunities in the increasingly open ASEAN labor market through the implementation of MRA Nursing 2025. While the MRA aims to enhance nurse mobility among ASEAN countries, Indonesian NERS graduates must compete with nurses from other ASEAN nations who are more experienced and possess international language proficiency. This study aims to explore the opportunities and challenges faced by Indonesian NERS graduates in competing in the ASEAN labor market and provide strategic recommendations to enhance their competitiveness. This research adopts a descriptive approach using both quantitative and qualitative methods. Data were collected through questionnaires distributed to NERS graduates across four regions in Indonesia and semi-structured interviews with purposively selected respondents. The findings show that Indonesian NERS graduates have strong technical competencies, but the greatest challenge lies in their limited foreign language skills, especially English. On the other hand, there are opportunities for Indonesian NERS graduates to improve their competitiveness through international training and the development of digital health skills. The study also finds that strengthening language and technical competencies, as well as obtaining international certification, are crucial for improving the position of Indonesian NERS graduates in the ASEAN labor market.